The Influence of Organizational Culture and Work Environment on Employee Performance Through Job Satisfaction in Pratama Tax Service Office Pasuruan - Surya Adhi Candra; M.Jamal Abdul Nasir; Sugeng Mulyono (Eduvest - Journal of Universal Studies, 2021)
The purpose of this study was to determine the effect of organizational culture and work environment on employee performance through job satisfaction. This research is a survey research using explanatory research type. The sample used was 106 respondents from the Pasuruan Pratama Tax Service Office. The sample in this study is the same as the population of data collection by means of a census. Statistical analysis used is Path Analysis approach. Calculation of the estimated values of the parameters is carried out with the help of the SPSS application. The results of the study show that: i) Organizational culture directly has a positive and significant influence on job satisfaction; ii) the work environment has no direct influence on job satisfaction; iii) Organizational culture directly has a positive and significant influence on employee performance; iv) work environment has no direct influence on employee performance v) job satisfaction has a positive and significant influence on employee performance; vi) organizational culture indirectly has an influence on employee performance through job satisfaction; (vii) the work environment does not indirectly have an influence on employee performance through job satisfaction.Effectiveness while the remaining 35.1% is influential with other factors not examined by the authors in this study.